1996
DOI: 10.1007/s002360050034
|View full text |Cite
|
Sign up to set email alerts
|

Possibility and impossibility results in a shared memory environment

Abstract: We focus on unreliable asynchronous shared memory model which support only atomic read and write operations. For such a model we provide a necessary condition for the solvability of problems in the presence of multiple undetectable crash failures. Also, by using game-theoretical notions, a necessary and sufficient condition is provided, for the solvability of problems in the presence of multiple undetectable initial failures (i.e., processes may fail only prior to the execution).Our results imply that many pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 21 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Taubenfeld and Moran [292] used a valency argument to provide a general impossibility result for a large class of problems in asynchronous systems with crash failures, where processes communicate using registers. In particular, they show that there is no f -resilient algorithm for the consensus problem restricted to input vectors in which the number of 0's and the number of 1's differ by at least f .…”
Section: Asynchronous Shared-memory Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taubenfeld and Moran [292] used a valency argument to provide a general impossibility result for a large class of problems in asynchronous systems with crash failures, where processes communicate using registers. In particular, they show that there is no f -resilient algorithm for the consensus problem restricted to input vectors in which the number of 0's and the number of 1's differ by at least f .…”
Section: Asynchronous Shared-memory Modelsmentioning
confidence: 99%
“…For example, a sharedmemory system can simulate a message-passing system with the same number of processes by using a single-writer single-reader register that can be written to by P and read by P to represent a communication channel from P to P [47,292]. Then, as mentioned in Sect.…”
Section: Relationships Between Modelsmentioning
confidence: 99%
“…Taubenfeld and Moran [1996] showed that binary consensus is solvable using a condition equivalent to this one.…”
mentioning
confidence: 92%
“…Agreement problems with a restricted set of inputs vectors were considered in Taubenfeld et al [1994] and Taubenfeld and Moran [1996], where possibility and impossibility results in a shared memory system and a hierarchy of problems that can be solved with up to f failures but not for ( f + 1) failures are introduced. More generally, an approach for designing algorithms in situations where there is some information about the typical conditions that are encountered when the respective problem is solved is presented in Berman and Garay [1998].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the idea to consider restricted sets of input vectors for consensus was stated for the first time in [27,28], where possibility and impossibility results in a shared memory system are presented. Moreover, these papers define a strict hierarchy of problems that can be solved in the presence of up to f failures but not in the presence of (f + 1) failures; they illustrate the hierarchy with variants of the consensus problem.…”
Section: Introductionmentioning
confidence: 99%